Comparing loss-on-ignition, acid decarbonation and combustion elemental analysis for measuring organic carbon concentrations – recommendations for best practice - Robert B. Sparkes; Stuart A. Rae; Lucy McMahon; Hannah L. Mossman; David McKendry; Clare E. Dean; Graham Tinsley; Frances Fowden; Connor J. Grisdale; Hafiza Begum; Holly Hope; Charlotte McEnhill; et al. (Organic Geochemistry, 2026)

Decolonising hydrology: Reflecting on positionalities for sustainable and just futures - Kwok P. Chun; Thanti Octavianti; Lori Bradford; Mark Reeves; Mohsen Nagheeby; Adeyemi Olusola; Ben C. Howard; Natalie Ceperley; Giulio Castelli; Albert Nkwasa; Yus Budiyono; Graham Strickert; et al. (Environmental Science & Policy, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Repeatability of critical thermal maximum (CTmax) in two freshwater ectotherms across contexts - Samuel D. Chasse; Erin M.C. Stewart; Graham D. Raby (Journal of Thermal Biology, 2025)

Developing Oak Buds Produce Volatile Emissions in Response to Herbivory by Freshly Hatched Caterpillars - Jessica L. Graham; Michael Staudt; Bruno Buatois; Samuel P. Caro (Journal of Chemical Ecology, 2024)

Seabird-vectored pelagic nutrients integrated into temperate intertidal rocky shores - Samuel Healing; Cassandra E. Benkwitt; Ruth E. Dunn; Nicholas A. J. Graham (Frontiers in Marine Science, 2024)
Seabirds provide inter-habitat connectivity by transporting vast quantities of nutrients from their pelagic feeding grounds to terrestrial and marine ecosystems via their nitrogen and phosphorous rich guano. However, it remains unclear whether seabird nutrients are cycling through many nearshore, temperate systems, such as United Kingdom (UK) rocky shores. Furthermore, it also remains unknown how seabird nutrient subsidies impact biodiversity, productivity, and recolonisation rates in UK rocky intertidal systems. Here, the impact of seabird nutrient subsidies to the Farne Islands, Northumberland, areas of high seabird densities during their breeding seasons, was compared to nearby low seabird density areas on the Northumberland coast. Estimated seabird derived nitrogen inputs and seabird densities were 420-1,025 and 949-2,279 times higher, respectively, on seabird islands than on the mainland. Seabird derived nutrient inputs led to substantially enriched nitrogen stable isotope (δ 15 N) values and total nitrogen content in terrestrial soil, plants, and lichen, and intertidal barnacles, and limpets, and higher δ 15 N values in macroalgae and turf algae. The seabird islands contained marginally greater algal species richness and higher densities of intertidal predators. However, other drivers could not be ruled out, such as nutrient inputs from mainland sources and marginally higher wave exposure at the mainland sites. No difference in limpet size, biomass, or abundance existed between the seabird islands and the mainland. On plots artificially cleared to simulate a disturbance event, barnacles recolonised faster on mainland sites. These findings provide evidence that seabird vectored pelagic nutrients are incorporated into terrestrial and intertidal ecosystems of UK islands, and therefore play an important role in facilitating ecosystem connectivity.

Small-scale fishing has affected abundance and size distributions of deepwater snappers and groupers in the MesoAmerican region - Ivy E. Baremore; Rachel T. Graham; Samuel R. D. Owen; Matthew J. Witt (Reviews in Fish Biology and Fisheries, 2023)
Deepwater fisheries in the Caribbean Sea are poorly studied and mostly unmanaged, despite their importance to local economies and food security. In the MesoAmerican region, deepwater fisheries are nearshore and easily accessible in many locations by small vessels, but historical and contemporary fishing effort varies by country. We used standardized fishery-independent methods, including vertical longlines and baited remote underwater video (BRUV) to assess the relative abundance and distribution of deepwater (100–550 m) snappers and groupers in Belize and Honduras. Fishery-dependent samples were used to supplement spatial distribution and body length data. Gathered data revealed that Belize, with a smaller fishing population and shorter history of deepwater fishing, had overall higher abundance of groupers and snappers and that fish were significantly larger than those in Honduras, which has a well-established and larger deepwater fishery. Water temperature was found to influence the abundance and occurrence of deepwater snappers more than depth. Deepwater snappers were widely-distributed throughout available habitat in both countries, but groupers were more patchy, and rarely encountered in the more heavily fished areas off Honduras. Our results suggest that a precautionary approach to fisheries management and targeted biological research of these stocks is required, which is particularly relevant for Belize, where climate change and overfishing mitigation measures are focused on an expansion of the deepwater fishery.

The Effects of Cooling on Fine-Grained Sandstone in Relation to Wellbore Injection of Carbon Dioxide - Nikolaos Reppas; Colin T. Davie; Yilin Gui; Ben Wetenhall; Samuel P. Graham (Rock Mechanics and Rock Engineering, 2023)
In Carbon Capture and Storage (CCS) procedures, it is important to determine the stability of the wellbore during carbon dioxide (CO 2 ) injection and part of this involves assessing stresses on the rock near the wellbore due to changes in temperature and pressure. To address this, this study investigated the influence of cooling on the mechanical properties of a sandstone typical of those found in the central and southern North Sea. A series of uniaxial and triaxial compression tests was conducted on dry and saturated sandstone samples to determine the effects of cooling on the strength and stiffness under different confining pressures. The elastic modulus, shear modulus, bulk modulus and Poisson’s ratio were determined for three temperature conditions and three pressures representing different depths in a wellbore. Two methods, the International Society of Rock Mechanics (ISRM) and Wood’s (Soil behaviour and critical state soil mechanics. Cambridge University Press, Cambridge, 1990), were used to determine the mechanical properties of the rock during the Uniaxial Compressive Strength (UCS) tests. For the triaxial test, only Wood’s (1990) method was applied due to the existence of confining pressure. Microstructural analysis on thin sections of the sandstones under plane and crossed polarised light conditions in the deformed and undeformed state was conducted to elucidate deformation mechanisms and aid interpretation of experimental results. It was identified that both an increase in confinement and a reduction in temperature, increased the strength of the sandstone and reduced the Poisson’s ratio. Additionally, by decreasing the temperature, especially in the UCS test the material dilated less. This is an important outcome as expanding the results to a wellbore stability problem, brittle behaviour may be more apparent and damage may occur when sub-zero injection temperatures are applied, especially at the wellbore head, where confinement is low.

The potential role of biofilms in promoting fouling formation in radioactive discharge pipelines - Franky Barton; Ben F. Spencer; Romain Tartèse; James Graham; Samuel Shaw; Katherine Morris; Jonathan R. Lloyd (Biofouling, 2023)

Constitutively Synergistic Multiagent Drug Formulations Targeting MERTK, FLT3, and BCL-2 for Treatment of AML - James M. Kelvin; Juhi Jain; Aashis Thapa; Min Qui; Lacey A. Birnbaum; Samuel G. Moore; Henry Zecca; Ryan J. Summers; Jeffrey M. Switchenko; Emma Costanza; Biaggio Uricoli; Xiaodong Wang; et al. (Pharmaceutical Research, 2023)

Ocular microtremor: a structured review - Lisa Graham; Julia Das; Rodrigo Vitorio; Claire McDonald; Richard Walker; Alan Godfrey; Rosie Morris; Samuel Stuart (Experimental Brain Research, 2023)
Ocular microtremor (OMT) is the smallest of three involuntary fixational micro eye movements, which has led to it being under researched in comparison. The link between OMT and brain function generates a strong rationale for further study as there is potential for its use as a biomarker in populations with neurological injury and disease. This structured review focused on populations previously studied, instrumentation used for measurement, commonly reported OMT outcomes, and recommendations concerning protocol design and future studies. Current methods of quantifying OMT will be reviewed to analyze their efficacy and efficiency and guide potential development and understanding of novel techniques. Electronic databases were systematically searched and compared with predetermined inclusion criteria. 216 articles were identified in the search and screened by two reviewers. 16 articles were included for review. Findings showed that piezoelectric probe is the most common method of measuring OMT, with fewer studies involving non-invasive approaches, such as contact lenses and laser imaging. OMT frequency was seen to be reduced during general anesthesia at loss of consciousness and in neurologically impaired participants when compared to healthy adults. We identified the need for a non-invasive technique for measuring OMT and highlight its potential in clinical applications as an objective biomarker for neurological assessments. We highlight the need for further research on the clinical validation of OMT to establish its potential to identify or predict a meaningful clinical or functional state, specifically, regarding accuracy, precision, and reliability of OMT.

Demand reduction and energy saving potential of thermal energy storage integrated heat pumps - Jason Hirschey; Zhenning Li; Kyle R. Gluesenkamp; Tim J. LaClair; Samuel Graham (International Journal of Refrigeration, 2023)

Revisiting Salvucci’s Semi-analytical Solution for Bare Soil Evaporation with New Consideration of Vapour Diffusion and Film Flow - Simon A. Mathias; Graham C. Sander; Jessica Leung; Samuel R. Newall (Transport in Porous Media, 2023)
Bare soil evaporation is controlled by a combination of capillary flow, vapour diffusion and film flow. Relevant analytical solutions mostly assume horizontal flow conditions and ignore gravitational effects. Salvucci (1997) provided a rare example of a semi-analytical solution for vertical bare soil evaporation. However, they did not explicitly represent vapour diffusion and film flow, which are likely to account for a significant proportion of total flow during vertical evaporation from soils. Vapour diffusion and film flow can be incorporated via Salvucci’s desorptivity parameter, which represents the proportionality constant relating Stage 2 cumulative evaporation to the square root of time under horizontal flow conditions. The objective of this article is to implement vapour diffusion and film flow within Salvucci’s semi-analytical solution and test its performance by comparison with isothermal numerical simulation and relevant experimental data. The following important conclusions are drawn. Analytical solutions that assume horizontal flow conditions are inadequate for understanding vertical evaporation problems because they overestimate evaporation rates and mostly predict vapour diffusion and film flow to be of negligible influence. Salvucci’s semi-analytical solution is effective at predicting the order-of-magnitude reduction in evaporation caused by gravitational effects. However, it is unable to identify the correct importance of vapour diffusion and film flow because these processes can only be represented through its desorptivity parameter.

Host plant resistance for fall armyworm management in maize: relevance, status and prospects in Africa and Asia - Boddupalli M. Prasanna; Anani Bruce; Yoseph Beyene; Dan Makumbi; Manje Gowda; Muhammad Asim; Samuel Martinelli; Graham P. Head; Srinivas Parimi (Theoretical and Applied Genetics, 2022)
Key message Sustainable control of fall armyworm (FAW) requires implementation of effective integrated pest management (IPM) strategies, with host plant resistance as a key component. Significant opportunities exist for developing and deploying elite maize cultivars with native genetic resistance and/or transgenic resistance for FAW control in both Africa and Asia. Abstract The fall armyworm [ Spodoptera frugiperda (J.E. Smith); FAW] has emerged as a serious pest since 2016 in Africa, and since 2018 in Asia, affecting the food security and livelihoods of millions of smallholder farmers, especially those growing maize. Sustainable control of FAW requires implementation of integrated pest management strategies, in which host plant resistance is one of the key components. Significant strides have been made in breeding elite maize lines and hybrids with native genetic resistance to FAW in Africa, based on the strong foundation of insect-resistant tropical germplasm developed at the International Maize and Wheat Improvement Center, Mexico. These efforts are further intensified to develop and deploy elite maize cultivars with native FAW tolerance/resistance and farmer-preferred traits suitable for diverse agro-ecologies in Africa and Asia. Independently, genetically modified Bt maize with resistance to FAW is already commercialized in South Africa, and in a few countries in Asia (Philippines and Vietnam), while efforts are being made to commercialize Bt maize events in additional countries in both Africa and Asia. In countries where Bt maize is commercialized, it is important to implement a robust insect resistance management strategy. Combinations of native genetic resistance and Bt maize also need to be explored as a path to more effective and sustainable host plant resistance options. We also highlight the critical gaps and priorities for host plant resistance research and development in maize, particularly in the context of sustainable FAW management in Africa and Asia.

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Bradyrhizobium centrolobii and Bradyrhizobium macuxiense sp. nov. isolated from Centrolobium paraense grown in soil of Amazonia, Brazil - Daniele C. Michel; Samuel R. Passos; Jean L. Simões-Araujo; Alexandre C. Baraúna; Krisle da Silva; Marcia M. Parma; Itamar S. Melo; Sofie E. De Meyer; Graham O’Hara; Jerri E. Zilli (Archives of Microbiology, 2017)

All in the family? Analyzing the impact of family history in addition to genotype on medullary thyroid carcinoma aggressiveness in MEN2A patients - Kristin L. Long; Carol Etzel; Thereasa Rich; Samuel Hyde; Nancy D. Perrier; Paul H. Graham; Jeffrey E. Lee; Mimi I. Hu; Gilbert J. Cote; Robert Gagel; Elizabeth G. Grubbs (Familial Cancer, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Increased Generation of Cyclopentenone Prostaglandins after Brain Ischemia and Their Role in Aggregation of Ubiquitinated Proteins in Neurons - Hao Liu; Wenjin Li; Muzamil Ahmad; Marie E. Rose; Tricia M. Miller; Mei Yu; Jie Chen; Jordan L. Pascoe; Samuel M. Poloyac; Robert W. Hickey; Steven H. Graham (Neurotoxicity Research, 2013)

A live weight–heart girth relationship for accurate dosing of east African shorthorn zebu cattle - Maia Lesosky; Sarah Dumas; Ilana Conradie; Ian Graham Handel; Amy Jennings; Samuel Thumbi; Phillip Toye; Barend Mark de Clare Bronsvoort (Tropical Animal Health and Production, 2012)

Robust Resampling Confidence Intervals for Empirical Variograms - Robert Graham Clark; Samuel Allingham (Mathematical Geosciences, 2011)